Implementasi Policy Base Routing dan Failover Menggunakan Router Mikrotik untuk Membagi Jalur Akses Internet di FMIPA Unnes - Ryo Pambudi; Much Aziz Muslim (Jurnal Teknologi dan Sistem Komputer, 2017)
Increasing requirement for information in every year become an important requirement for every society, organizations, and others institution. Semarang State University (Unnes) had using online information systems in every aspect. It needs high speed and reliable internet connection, so the using of two Internet Service Provider (ISP) or public pathways are highly commended. Internet access point density due to the number of users such as students, faculty, and employees to be one of the factors that can interfere with such information systems. Routing settings on Mikrotik router become one of the solutions to reduce density access to the Internet. The function of policy-based routing is to separate the path which will be passed when the accessing the Internet and the function of failover technique is to move path automatically if one access point (ISP) impaired / down. Comparison before and after applying these two techniques while accessing the Unnes information systems results increasing access speed with 4 ms response time faster than before used policy-based routing.